DATES OF DÉTERMINATION OF MAIZE SEEDLING (ZEA MAYS L.) ON THE TROPICAL FERRUGINOUS IN THE CENTRAL REGION OF BENIN : CASE STUDY OF THE ADMINISTRATIVE DISTRICT OF GLAZOUE AND DASSA-ZOUME - Batamoussi, Michel Hermann; Sekloka, Emanuel; Oga, Codjo Amour; Boulga, Julien; Paraïso, Armand (European Scientific Journal, ESJ, 2014)
Bénin’s economy is chiefly focused on agriculture. This agriculture is characterized by a great diversity and the cereals occupy a great part of it having maize as the lead. Many constraints prevent the producers from increasing the outputs of the maize seed, among these constraints there are climate changes characterized by the irregularity and bad distribution of the rainfalls. To face this challenge one needs to take several precautions among which the adaptation of the dates of seedling to the new climatic situation. The aim of our research work is to assess the impact of the different dates of seedling on the agronomic parameters on the cultivation of maize and more specifically on DMR variety. The research works have been conducted in the physical environment in the centre of the country in the villages of Gome and Miniffi, respectively in the administrative district of Glazoué and Dassa- Zoumé. The experiment includes four different dates of seedling: S1 (31 May), S2 (10 June), S3 (20 June) and S4 (30 June). The assessed agronomic parameters are related to the growth in height and circumference to the collar of the plants, the foliar surface, the physiological parameters the outputs of the maize and the weight of 1000 grains. The obtained results show that the dates of seedling have had a significant impact (p < 0,05) on the growth in height of the plants of the maize when the sizes are done 40, 50,60 days after the seedling. DAS As for the circumference to the collar, the impact of the seedling dates has been on the other hand insignificant (p > 0, 05), to 40, 50, and 60 DAS and significant (p < 0, 05) to70 DAS. The seedling dates have significantly influenced all the studied physiological parameters except the 1th male inflorescences and the foliar sizes of the plants of maize as well at 30 DAS until 60 DAS. During the harvest, the seedling date S1 (31 May) has permitted to obtain the best output of grain (2,43vs; 1,7vs; 1,7vs; 2,0t/ha) in accordance with the dates of the seedling S2 ; S3 ; and S4 respectively.